The study on the challenges and strategies of Taiwanese enterprises in China during 2007–2008: a text mining analysis. (1st January 2012) - Guo, J.J.; Wu, S.H.
In recent years, the volume of cross strait investment and trade between China and Taiwan has considerably increased after the accession to the WTO. During 2007 to 2008, Taiwanese enterprises in China began to face the challenges from Chinese government's policy change. In order to remain competitive, Taiwanese enterprises took some measures to cope with the challenges. In order to comprehend the Chinese policy change effects on Taiwanese enterprises, this paper made the depth interviews and applied the text mining analysis to the interviews responses. Through applying the text mining analysis, the study found the policy change of the Labour Contract Law and the increased cost had larger effect on Taiwanese enterprises.